Internal exposure of medical staff – should it be monitored? - Filipiak, Bogdan; Mlicki, Kazimierz; Haratym, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 1999)
The specific problem of radiation protection in medicine is discussed. The exposure of medical staff working with open radiation sources requires the optimisation. Important part of this optimisation is the determination of effective dose, connected with the monitoring of individual internal exposure. Purpose of this paper is to initicte discussion on the subiect.